Sense and Sensitivity - Leong, Dawn-joy; Phillips, Simon; Ellis, Katie; Girdler, Sonya; D'Arcy, Emily; Fyfe, Jordan (Curtin Autism Research Group and Curtin Centre for Culture & Technology, 2021)
Sense and Sensitivity celebrates the unique sensorial place of autistic artistry in the world via the lens of autistic landscape photographer, Simon Phillips, and the deep listening of autistic performance artist Dawn-joy Leong. In a kaleidoscope of beautiful imagery and subtle sound, this remarkable collaboration privileges the feelings of both artists for the world; how they engage with it through what they see, hear and touch; revealing their exquisite appreciation for themes of diversity, balance, place and timelessness.